Systematic review of the quality of the cross-cultural adaptations of Disabilities of the Arm, Shoulder and Hand (DASH): Systematic Review of the Cross-Cultural Adaptations of DASH - Sigirtmac, Ilkem Ceren; Oksuz, Cigdem (La Medicina del Lavoro, 2021)
Background: The Disabilities of the Arm, Shoulder and Hand (DASH) Outcome Measure is a widely used patient reported outcome measure. Objective: The aim of this study is to evaluate the quality of translation procedures and assessment of the psychometric properties of cross-cultural adaptations of the DASH. Methods: We reviewed the literature to identify all published studies of cultural adaptations of the DASH questionnaire. For the quality assessment, we used Guidelines for the Process of Cross-Cultural Adaptation of Self-Report Measures, Quality Criteria for Psychometric Properties of Health Status Questionnaire and COSMIN Checklist for Cross-Cultural Validity. Results: We included 25 articles with 26 versions of the DASH. Only the Puerto Rican version followed all six of the processes of cross-cultural adaptation. None of the versions assessed all eight measurement properties for Quality Criteria for Psychometric Properties of Health Status Questionnaire and none of them had a positive rating from agreement, internal consistency, responsiveness and interpretability. All the studies got a poor rating according to the COSMIN checklist. Discussion: None of the versions got a good rating from all three checklists. We observed that supplementary tests for the adaptations are necessary, especially for assessing agreement, responsiveness and interpretability. We concluded that all versions need more research on psychometric properties.